Penerjemahan Partikel “Min” dalam Kitab Al-Barzanji: Kajian Nahwu dan Kesepadanan Terjemah Arab – Indonesia / The Translation of the Particle “Min” in the Book of Al-Barzanji: A Study of Grammar and Translation Equivalence Arabic – Indonesian - Ovi Siti Nuropikoh; Akmaliyah Akmaliyah; Wildan Taufiq (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study examines the issue of the particle min (من) in the translation of classical religious texts. Translators often interpret this particle simply as “from,” thereby failing to convey the complexity of its semantic function. This study aims to identify the various nahwu functions of the particle min (من) in the al-barzanji text and analyze its implications for translation strategies and techniques into Indonesian. This study uses a descriptive qualitative approach with content analysis methods. The researcher collected all data on the occurrence of the particle min (من) in the text. then grouped it based on its grammatical function. The researcher analyzed the data referring to classical nahwu theory, Eugene Nida's equivalence theory, and the translation techniques proposed by Molina and Hurtado Albir. The results of the study show that the particle min represents five main functions, namely ibtidā’ al-ghāyah, tab‘īḍ, bayān al-jins, ta‘līl, and zā’idah. In translation practice, translators use literal, modulation, amplification, reduction, and common equivalent techniques with a tendency to move between formal equivalence and dynamic equivalence.Penelitian ini mengkaji persoalan partikel min (من) dalam penerjemahan teks religius klasik. Penerjemah sering memaknai partikel tersebut secara tunggal sebagai “dari”, sehingga kompleksitas fungsi semantisnya menjadi kurang tergambar. Penelitian ini bertujuan untuk mengidentifikasi ragam fungsi nahwu partikel min (من) dalam teks al-barzanji serta menganalisis implikasinya terhadap strategi dan teknik penerjemahannya ke dalam bahasa Indonesia. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis isi. Peneliti mengumpulkan seluruh data kemunculan partikel min (من) dalam teks, kemudian mengelompokkannya berdasarkan fungsi gramatikal. Peneliti menganalisis data tersebut dengan merujuk pada teori nahwu klasik, teori kesepadanan Eugene Nida, serta teknik penerjemahan yang dikemukakan oleh Molina dan Hurtado Albir. Hasil penelitian menunjukkan bahwa partikel min merepresentasikan lima fungsi utama, yaitu ibtidā’ al-ghāyah, tab‘īḍ, bayān al-jins, ta‘līl, dan zā’idah. Dalam praktik penerjemahan, penerjemah menggunakan teknik literal, modulasi, amplifikasi, reduksi, dan padanan lazim dengan kecenderungan bergerak antara kesepadanan formal dan kesepadanan dinamis.